Lumbosacral plexopathy – An unusual presentation of sciatic endometriosis (Indian Journal of Case Reports, 2020)
Endometriosis is a common gynecologic disorder that presents with chronic pelvic pain or infertility. It is the presence of endometrial tissue outside the uterus. It is typically present in the pelvis, such as on the ovaries and pelvic peritoneum. It may also involve the bowel, ureter or bladder, and the neurovascular bundle in the leg. We, hereby, report that the case of a lady who presented to us with catamenial leg pain on her right side was diagnosed to have lumbosacral plexopathy with underlying etiology as endometriosis on evaluation, an unusual presentation of a disease.